IEEE International Digest of Technical Papers on Magnetics Conference
DOI: 10.1109/intmag.2002.1001096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of asymmetry in far fields of permanent magnet motors

Abstract: Abstruct-Permanent magnet machines are being considered for use in electric ships as pumps and drives. The exterior fields of these machines are of concern. These fields decay at a rate that depends on the number of poles, fields from higher number of poles decaying more rapidly. If there is an imbalance in the set of poles, the lower order decay of the unbalanced poles dominate in the far field and the advantage of using a high number of poles could be lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The scalar magnetic potential generated at the basis boundary by both the magnet and yoke is calculated by the authors at RPI [5] using a full FE (FLUX 3D) model shown in Fig. 3 and the partial FE model (ANSYS) of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The scalar magnetic potential generated at the basis boundary by both the magnet and yoke is calculated by the authors at RPI [5] using a full FE (FLUX 3D) model shown in Fig. 3 and the partial FE model (ANSYS) of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The simplest model of equivalent source which has been proposed is a magnetic dipole (Yamazaki and Kawamoto, 2001;Zaffanella et al, 1997). However, a simple dipole may be not representative enough of the field distribution, depending upon the kind of the appliance (Salomon and O-Mun, 2001), and on the distance from it. In this case, a multipolar source can be used.…”
Section: Introductionmentioning
confidence: 99%